2019
DOI: 10.1111/cod.13322
|View full text |Cite
|
Sign up to set email alerts
|

New positive patch test reactions on day 7—The additional value of the day 7 patch test reading

Abstract: Background Not performing a day (D) 7 patch test reading might result in positive patch test reactions being missed. Objectives To investigate the added value of the D7 patch test reading for individual allergens, and to identify patient characteristics and allergen groups associated with new positive D7 reactions. Methods Data from patients patch tested between 2008 and 2018 with the extended European baseline series were analysed. Patch test readings were performed on D3 and D7. Positive reactions were categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
7
39
4
Order By: Relevance
“…The value of a clinical reading performed on D7 has been discussed by several research groups. Although some studies strongly recommend a D7 reading for all allergen series, others only find it important for allergens such as metals, topical antibiotics, and acrylates 4,5,7‐9,26,27 . In our study, 6.3% of all positive reactions were found on D7 only, comprising nickel, formaldehyde, cobalt, gold, and budesonide as the most frequent causative allergens in accordance with previous findings 4,5,7‐9,26,27 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The value of a clinical reading performed on D7 has been discussed by several research groups. Although some studies strongly recommend a D7 reading for all allergen series, others only find it important for allergens such as metals, topical antibiotics, and acrylates 4,5,7‐9,26,27 . In our study, 6.3% of all positive reactions were found on D7 only, comprising nickel, formaldehyde, cobalt, gold, and budesonide as the most frequent causative allergens in accordance with previous findings 4,5,7‐9,26,27 .…”
Section: Discussionsupporting
confidence: 90%
“…Van Amerongen et al found 13.6% new positive reactions on D7 in patients tested with allergens from the European Baseline Series, TRUE Test, and additional unspecified allergens chosen by the investigator through a 10‐year period. Cantwell et al found approximately 30% new positive reactions on D7 in 411 patients tested with multiple series, whereas Madsen et al reported 4.4% new positive reactions on D7 in patients with hand eczema who were tested with TRUE Test only 4,8,27 . Because we included the European Baseline Series and TRUE Test only, the prevalence of late reactions in our study may have been even higher if additional series had been included in the assessment.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…7 Furthermore, by adding a patch test reading on D7 to the D3/D4 reading, an additional 3%-34% of sensitized cases can be identified. 8 When it comes to (meth)acrylates, late reactions are well known, with about 10% of positive reactions occurring first on reading D7 or later, [9][10][11] without being cases of active sensitization. 10 Thus, a patch test reading on D7 is mandatory to increase diagnostic accuracy.…”
Section: Patch Testing and Diagnosis When Suspecting Allergic Contactmentioning
confidence: 99%
“…A 2019 analysis of the prevalence of new patch test reactions on day 7 showed that 17% of 607 patients were negative on day 3 but were positive on day 7, further emphasizing the importance of a properly timed delayed reading. 12…”
Section: Patch Testing To Nickelmentioning
confidence: 99%